Comparative efficacies of modules against major insect pests and natural enemies in rice (Oryza sativa) - SENI, ATANU; MISHRA, K M; PAL, RINI (The Indian Journal of Agricultural Sciences, 2022)
A field experiment was conducted at regional Research and Technology Transfer Station (OUAT), Chiplima,Sambalpur, Odisha, during rainy season (kharif) 2019–20 to determine the comparative efficacies of variousinsecticides and botanicals modules against major insect pests and natural enemies of rice (Oryza sativa L.). Therewere 9 modules and overall data revealed that the all the treated plots recorded significantly lower per cent of deadheart; white ear-head caused by stem borer; silver shoot caused by gall midge; leaf folder infested leaves and planthoppers. Among them, module consists of fipronil 5 sc @1500 ml/ha at 25–30 DAT, rynaxypyr 20 sc @150 ml/ha at45–50 DAT and triflumezopyrim 106 sc @240 ml/ha at 65–70 DAT treated plot recorded significantly higher per centreduction of stem borer infestation, leaf folder, plant hoppers and produced higher grain yield than the other modules as well as highest benefit cost ratio B : C (1.89) and next best was carbosulfan 25 ec @875 ml/ha, rynaxypyr 20 sc @150 ml/ha and flonicamid 50 wg @150 g/ha containing module. So, the module containing fipronil, rynaxypyr and triflumezopyrim may be adopted for the effective management of major insect pests of rice and helps the farmers from unwanted spraying of insecticides many times.